(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
This article covers the fact that young people should be protected from becoming the victims of illiteracy and violence in the family which consequently causes negative effect on their future life and unknowingly committing the crime and taught the essential role of the family and correct parenting in upbringing of well-bred children.